Common and distinctive linguocultural features of the concepts of nationality and personality in the English and Uzbek languages - Burieva, Nilufar (The Lingua Spectrum, 2025)
The article deals with the issues based on the common and distinctive linguocultural features of the concepts of nationality and personality in the English and Uzbek languages. It analyzes how these concepts are verbalized through lexical, phraseological, and cultural means, reflecting each nation’s worldview, traditions, and value system. The study emphasizes that in English, the concept of nationality is often associated with individualism, self-expression, and civic identity, while in Uzbek linguoculture it is closely linked to collectivism, respect for ancestry, and moral integrity. Similarly, the concept of personality demonstrates different evaluative and cultural nuances, shaped by historical, social, and ethical contexts. Comparative analysis reveals both universal human values and culturally specific features in the linguistic representation of these notions. The findings contribute to intercultural communication studies, support the understanding of cross-cultural differences, and highlight the importance of national mentality and cultural background in understanding linguistic worldviews in both English and Uzbek societies.